Synthesis and Characterization of Low-Cost Epoxy-Based Erosion Resistant Nanocomposite Coating - S. Imran Ali,; S. Rizwan Ali,; M. Naeem,; Shadrukh Abdul Haq,; Muhammad Mashhood,; Ammad Ali ,; S. Adnan Hasan, (Journal of Basic & Applied Sciences, 2016)
We report a simple route to synthesized erosion resistant epoxy-based nanocomposite coatings. The silica nanoparticles were surfaced modified using stearic acid and then incorporated into the epoxy coating. The resulting nanocomposite coating films were characterized for erosion resistance, mechanical and thermal stability. For the application on turbine blades, conventional techniques were used. It was found that for the incorporation of nano silica into the epoxy matrix, surface modification was essential. Besides, incorporation of silica resulted in considerable improvement in the resistance to erosive wear and a life span improvement of around 36 percent was achieved. Similar trend was observed for the Shore D hardness which increases from 60 for the virgin coating to 70 for the nanocomposite coating.